2003
DOI: 10.1111/1468-0297.00117
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Vulnerability

Abstract: Traditional poverty measures neglect several important dimensions of household welfare. In this paper we construct a measure of 'vulnerability' which allows us to quantify the welfare loss associated with poverty as well as the loss associated with any of a variety of different sources of uncertainty. Applying our measure to a panel dataset from Bulgaria in 1994, we find that poverty and risk play roughly equal roles in reducing welfare. Aggregate shocks are more important than idiosyncratic sources of risk, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
169
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(177 citation statements)
references
References 7 publications
3
169
3
2
Order By: Relevance
“…Some studies on vulnerability have used panel data collected over a long period due to the forward-looking nature of the concept of vulnerability [11,25]. However, other studies have shown that cross section data can also be used in estimating vulnerability to poverty [12,14,16,26-29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies on vulnerability have used panel data collected over a long period due to the forward-looking nature of the concept of vulnerability [11,25]. However, other studies have shown that cross section data can also be used in estimating vulnerability to poverty [12,14,16,26-29].…”
Section: Methodsmentioning
confidence: 99%
“…Vulnerability to poverty is seen widely as a better future oriented/forward-looking measure of welfare [11-15]. The only study that analysed ex-ante welfare or vulnerability to poverty in Ghana did not consider the impact of health shocks [16].…”
Section: Introductionmentioning
confidence: 99%
“…3 Since poverty is such a widely used and recognized indicator of socioeconomic status, and because expected poverty has a cardinal interpretation and is more easily interpretable than utility-based measures (e.g., the measure proposed by Ligon and Schechter, 2003), conceptualizing vulnerability in terms of expected poverty seems a reasonable route to take in assessing ex ante household welfare. Using the poverty headcount ratio introduced in Foster et al (1984), it can be shown that vulnerability as expected poverty reduces to simply the cumulative distribution of income below the poverty line, or simply the probability of poverty.…”
Section: The Measurement Of Vulnerabilitymentioning
confidence: 99%
“…In addition, women are at more risk of contagious diseases due to their closer contact with the sick family members. Other evidences showed that gender of the head of household have no effect on the vulnerability, but those households are subjected to greater aggregate risks (Ligon and Schechter, 2003).…”
Section: Dpm 234mentioning
confidence: 99%